PSYCHOLINGUISTIC ANALYSIS OF THE LANGUAGE DISORDERS OF THE MAIN CHARACTER WITH MENTAL DISABILITIES IN THE FILM "I AM SAM" - Sri Suzanna Putri Bakhtiar; Murni Mahmud; Mardiyanah Nasta (Journal of English Literature and Linguistic Studies, 2026)
This study aims to analyze the language disorders experienced by the main character with mental disabilities and the impact of these disorders on his social interactions in the film I Am Sam through a psycholinguistic approach. This study uses Bloom & Lahey's (1978) theory of language disorders and Vygotsky's (1978) theory of social interaction and a psycholinguistic approach that focuses on the relationship between mental processes and individual language abilities. This study uses a descriptive qualitative method with data collection techniques in the form of observations of dialogues and scenes in the film that represent symptoms of language disorders. The results of the study show that Sam experiences several forms of language disorders, including receptive language disorder, expressive language disorder, and pragmatic language disorder. Sam's language disorder has a significant impact on his ability to interact socially, where he often experiences misunderstandings, limitations in expressing emotions, and dependence on his immediate social environment. These findings reinforce the understanding that cognitive limitations due to mental disabilities greatly affect language aspects, both receptively and productively.